(untitled) (Journal Of Educational and Psychological Researches, 2023)
Abstract This research aims to identify the availability of the elements of the concept of citizenship, to identify the distribution ratios of the outputs of the musical skills curriculum at the levels of educational goals associated with the elements of the concept of citizenship in the guides of teachers of musical skills for grades (12-1) in the Sultanate of Oman. A content analysis card was designed to include the teacher’s guides of musical skills for grades (12-1), which included the outputs, according to the grades with the identification of the elements of citizenship (identity, belonging, rights, participation). The results of the research revealed that the percentage of inclusion of citizenship values in the evidence is excellent, which is attributed to the authors of the curriculum who look at citizenship from a cultural aspect related to the musical heritage, folklore, and the instruments that are used to present this folklore, but they did not link it to aspects related to rights. 41.0% for grades (5-1), while in grades (12-6) the largest percentage was in the level of remembrance at (51.5%). This is attributed to the strengthening of citizenship and its four elements through musical skills. It is a complex and multi-dimensional idea, and music is also seen as requiring multiple levels of knowledge, especially in the areas of application, installation, and evaluation. One of the most important recommendations of the research is to increase the percentage of inclusion of citizenship values in the guides for teachers of musical skills in the Sultanate of Oman.